Porous geopolymer, preparation method thereof, phase-change composite material and application of phase-change composite material

By synthesizing a graded porous geological polymer with elosite and superhydrophobic modification, the problems of inappropriate porous support packaging phase change materials in the prior art are solved, and higher packaging volume and heat storage stability are achieved.

CN119822701APending Publication Date: 2025-04-15ZHENGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510054373.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

In the prior art, porous carriers are used to encapsulate phase change materials with problems such as inappropriate pore size, high cost, complex preparation process and low packaging rate, resulting in a smaller heat storage density of phase change materials.

Method used

By synthesizing graded porous geological polymers with elosteite and superhydrophobic modification, the performance of its encapsulated phase change materials and its ability to cope with harsh application environments. Specific methods include calcining elucidite to prepare partial elucidite, chemical foaming to prepare porous foam geological polymers, and superhydrophobic modification by vapor-phase deposition of polydimethylsiloxane.

Benefits of technology

It improves the packaging volume and heat storage stability of phase change materials, reduces leakage risk, and enhances the moisture-proof and self-cleaning capabilities of the materials, and is suitable for various harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822701A_ABST
    Figure CN119822701A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of inorganic nonmetal gelling, in particular to a porous geopolymer and a preparation method thereof, and a phase change composite material and application thereof. The preparation method of the porous geopolymer comprises the following steps: preparing metahalloysite (MHNT) with geopolymerization activity, preparing an MHNT-based porous foam geopolymer through chemical foaming, and obtaining the super-hydrophobic porous geopolymer through vapor deposition of polydimethylsiloxane. The phase-change composite material is obtained by encapsulating a phase-change material with a porous geopolymer. The porous foam geopolymer is prepared by adopting an alkali excitation method, and the reaction process is simple and easy to control. In addition, no by-product is generated in the reaction process, the method is environment-friendly and pollution-free, large-scale preparation can be realized, and the method is convenient to produce; according to the method, a multi-stage porous structure is generated by foaming the hollow glass microspheres and H2O2, the packaging amount can reach 50-53%, and the packaging amount of the phase change material is greatly increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of inorganic non-metallic gelling, in particular to porous geopolymer and a preparation method thereof, phase change composite material and application thereof. Background Art

[0002] Energy shortage and environmental pollution are important issues facing today's society. Developing and utilizing renewable green energy and improving energy utilization are of great significance to energy conservation and environmental protection. Renewable energy sources such as solar energy, wind energy, and biomass energy that can replace traditional fossil fuels generally have intermittent and volatile energy transmission, and often have problems with mismatches in supply and demand in time, intensity, and space. Developing energy storage technology to collect this energy and release it when needed can effectively solve the contradiction between energy supply and demand and improve energy utilization.

[0003] Phase change energy storage is an effective way to store thermal energy. The purpose of energy storage and release can be achieved by using the phase change of phase change materials (PCM) to absorb or release heat from the environment. Due to the advantages of high energy storage density, reusability and easy temperature control, phase change materials have been widely used in solar energy collection, heating, air conditioning, civil buildings, smart fabrics, waste heat and waste heat recovery. Phase change materials can be divided into inorganic phase change materials and organic phase change materials according to their chemical composition. Inorganic phase change materials such as hydrated salts have high thermal conductivity and heat storage capacity, but they are prone to phase separation during the phase change process, which greatly reduces their service life. In contrast, organic phase change materials have excellent stability and can still maintain stable phase change latent heat after multiple cycles of heat storage and heat release, but the shape of organic phase change materials is unstable during the phase change process and liquid phase leakage is prone to occur.

[0004] The use of porous structural materials to encapsulate phase change materials, store liquids through porous structures and restrict the flow of liquid phase, can effectively solve the problems of unstable morphology and liquid phase leakage of phase change materials. Commonly used carriers include metal organic frameworks, metal foams and carbon nanotubes, etc. However, metal organic frameworks and metal foams are easily corroded, have high costs and complex preparation processes, and metal foams generally have large pore sizes, which are prone to leakage when the encapsulation amount is high, which seriously restricts their further application development; while the pores of carbon nanotubes are fine, which makes it difficult to effectively load and encapsulate phase change materials inside them. Special methods are often required to modify them to improve their encapsulation performance, and they are expensive, which greatly limits their large-scale application. Therefore, it is crucial to find a cheap, high-porosity, and suitable-pore-size porous carrier for the encapsulation of phase change materials. Geopolymer is an inorganic polymer with a pore structure similar to that of zeolite. It has rich pores, high temperature resistance, fire resistance, high compressive and tensile strength, strong chemical stability, simple preparation method, and cheap and easy-to-obtain raw materials, making it one of the ideal carriers for encapsulating phase change materials.

[0005] Natural aluminosilicate mineral materials are one of the common raw materials for preparing geopolymers. There are a large number of hydroxyl groups in natural aluminosilicate mineral materials, which can form chemical bonds with aluminum atoms, etc. The existence of these chemical bonds limits their ability to directly participate in geopolymerization reactions. After dehydroxylation, the chemical bonds are destroyed, and a large number of active sites for geopolymerization reactions can be generated. Halloysite nanotubes (HNTs) are a tubular structure of polyhydrated aluminosilicate mineral materials, and their chemical composition is similar to that of kaolinite. Although the reserves of halloysite nanotube deposits around the world are very large, due to the relatively little research on halloysite nanotubes in history, they have not been widely used. Compared with kaolinite, halloysite has the following advantages: halloysite has a higher surface area and structural disorder than kaolinite; halloysite nanotubes have unique morphology, high surface reactivity and hydrophilicity; the temperature required for the dehydroxylation of halloysite is lower than that of kaolinite, so the dehydroxylation process consumes less energy (Appliedclay science, 2020, 185, 105375); halloysite has higher geopolymer activity (Cement & Concrete Composites, 2012, 34, 709-715), is widely available and inexpensive, so it can be used as an ideal raw material for the preparation of geopolymers.

[0006] At present, the preparation methods of porous geopolymers are generally divided into pre-foaming method and chemical foaming method. The pre-foaming method is to mix the prefabricated foam generated by rapid stirring of the surfactant solution with the geopolymer slurry. Although this method can obtain a uniform pore structure, there may be a risk of defoaming as the external temperature, air pressure, etc. change. The chemical foaming method is to add substances that can produce gas during the chemical reaction process, but the porous structure obtained by this method is not easy to control, and the pore size distribution is relatively uneven. In addition, in the current literature on geopolymer encapsulation of phase change materials, phase change materials or phase change material microcapsules are usually added as additives to geopolymer slurry, and the phase change material is encapsulated inside as the geopolymer solidifies, and the encapsulation amount is generally around 10-20% (Energy, 2023, 278, 127624; SolarEnergy, 2019, 181, 464-474; Construction and Building Materials, 2023, 386, 131570). Compared with aerogel, porous carbon, metal foam, etc., its encapsulation rate is very low, resulting in a low heat storage density. Therefore, it is necessary to improve the preparation method and encapsulation method of geopolymers so that they have a larger pore volume and can encapsulate more phase change materials. Summary of the invention

[0007] The purpose of the present invention is to overcome the existing technical problems, use halloysite to synthesize hierarchical porous geopolymers and perform superhydrophobic modification to improve the performance of encapsulating phase change materials and the ability to cope with harsh application environments. To achieve the purpose of the present invention, the technical solution adopted is as follows:

[0008] To achieve the above object, the present invention is implemented according to the following technical solutions:

[0009] The method for preparing porous geopolymer comprises the following steps:

[0010] S1, Preparation of geopolymerizable heliumite

[0011] Halloysite (HNT) is calcined in an air atmosphere to obtain meta-haloysite, which is denoted as MHNT;

[0012] S2, Preparation of MHNT-based porous foam geopolymer by chemical foaming

[0013] S2.1, dispersing MHNT and hollow glass microspheres in an alkali activator, adding a nonionic surfactant and a hydrogen peroxide aqueous solution, and mixing them evenly to obtain a MHNT-based geopolymer slurry;

[0014] S2.2, pouring the MHNT-based geopolymer slurry into a mold, leaving it at room temperature until it is completely foamed and expanded, and then transferring it to an oven for curing, and obtaining a cured product after the curing is completed;

[0015] S2.3, neutralizing the solidified product with an acid solution, washing and drying the product after neutralization to obtain a MHNT-based porous foam geopolymer, denoted as MH;

[0016] S3: Superhydrophobic porous geopolymers obtained by vapor deposition of polydimethylsiloxane (PDMS)

[0017] After MH is fully contacted with an excess of polydimethylsiloxane and then heated, a superhydrophobic porous geopolymer is obtained, which is denoted as PMH.

[0018] Preferably, in step S1, the calcination temperature is 650-850° C. and the calcination time is 3 hours.

[0019] Preferably, in step S2.1, the mass ratio of MHNT to hollow glass microspheres is (1-4):1;

[0020] In the step S2.1, MHNT and hollow glass microspheres are both solid raw materials;

[0021] The amount of the nonionic surfactant used is 0.1-0.5% of the total mass of the solid raw material; the concentration of the hydrogen peroxide aqueous solution is 30wt%, and the amount used is 5-10% of the total mass of the solid raw material; in the alkaline activator, the molar ratio of SiO2, Na2O, and H2O is 1.38:1:15.74;

[0022] The mass volume ratio of the solid raw material to the alkali activator is 1:1.5, and the unit of the mass volume ratio is g:mL;

[0023] In step S2.2, the standing time is 10-24 hours; the curing temperature is 50-80°C;

[0024] In step S2.3, the acid solution is a 1M hydrochloric acid solution; deionized water is used for multiple washings during the washing process; the drying temperature is 60° C., and the drying time is 12 hours.

[0025] Preferably, in step S2.1, the hollow glass microspheres are soda lime borosilicate glass microspheres with a diameter of 20-75 μm; the nonionic surfactant is F 108.

[0026] Preferably, the alkali activator is obtained by dissolving sodium hydroxide or water glass in water or deionized water and stirring until clear and transparent.

[0027] Preferably, in step S3, the heating process is carried out under the protection of an inert atmosphere, the heating temperature is 250-450° C., and the heating time is 3 hours.

[0028] The present invention also includes the porous geopolymer prepared by the above preparation method.

[0029] Specifically, the method for preparing porous geopolymer comprises the following steps:

[0030] S1: Preparation of geopolymer-active heliumite MHNTs

[0031] The HNT was calcined at 650-850°C for 3 h in an air atmosphere to dehydroxylate the HNT to obtain the meta-halloysite MHNT;

[0032] S2: Preparation of MHNT-based porous geopolymer foams by chemical foaming

[0033] A certain amount of sodium hydroxide and water glass are dissolved in a certain amount of deionized water or water so that the molar ratio of SiO2, Na2O, and H2O is 1.38:1:15.74, mixed thoroughly and allowed to stand at room temperature until the solution is clear, thereby obtaining an alkali activator;

[0034] Then, MHNT and hollow glass microspheres in a mass ratio of (1-4) : 1 are dispersed in the above-mentioned alkali activator, and then a non-ionic surfactant is added in an amount of 0.1-0.5% of the total mass of the solid raw materials. F108 and 5-10% of the total mass of the solid raw material 30wt% H2O2 aqueous solution; the mass volume ratio of the solid raw material to the alkali activator is 1:1.5, and the unit of the mass volume ratio is g:mL; the above mixture is stirred with a glass rod until it is mixed uniformly to obtain MHNT-based geopolymer slurry;

[0035] Then pour it into a cylindrical silicone mold (diameter × height = 30 mm × 15 mm) and cover it with plastic wrap to prevent water evaporation; leave the sample at room temperature for 10-24 h to fully bubble and expand, and then transfer it to a high-temperature oven at 50-80 ° C for rapid curing;

[0036] After curing, the sample was removed from the mold and neutralized in an excess of 1 M hydrochloric acid solution to remove excess alkali; subsequently, the sample was washed with deionized water several times and dried overnight to obtain MHNT-based porous foam geopolymer MH;

[0037] S3: Obtaining Superhydrophobic Porous Geopolymer PMH by Vapor Deposition of PDMS

[0038] The dried MH was immersed in excess PDMS to make it fully contact with PDMS, and then the sample was placed in a heating and cooling state with a rate of 5 °C min -1 The samples were placed in a tube furnace and heated at 250-450 °C in an Ar gas environment for 3 h. The obtained samples were denoted as PMH.

[0039] The present invention also includes a phase change composite material, which is obtained by encapsulating the phase change material in the porous geopolymer.

[0040] Preferably, the phase change material is one of paraffin wax (PW), stearic acid (SA), lauric acid (LA), and myristic acid (MA).

[0041] Preferably, the packaging is performed by vacuum impregnation.

[0042] Preferably, the packaging process is: placing excess phase change material and porous geopolymer into a container, placing the container into a vacuum oven at a temperature higher than the melting temperature of the phase change material; when all the phase change materials are completely melted, evacuating the vacuum oven for 30-60 minutes; then removing excess phase change material and cooling to obtain a phase change composite material (also referred to as PMH phase change composite material).

[0043] Phase change materials are encapsulated in PMH by vacuum impregnation under the action of capillary attraction, surface tension, diffusion and adsorption. Under vacuum, phase change materials can gradually penetrate into the pores of PMH porous geopolymers.

[0044] The container used in the above packaging process can be a glass beaker.

[0045] Specifically, the preparation method of the phase change composite material includes the following steps:

[0046] Phase change materials (PW, SA, LA, MA) are encapsulated in PMH by vacuum impregnation under the action of capillary attraction, surface tension, diffusion and adsorption. The specific process is: put excess phase change materials and PMH into a glass beaker and put it into a vacuum oven with a temperature higher than the melting temperature of the phase change material. When all the phase change materials are completely melted, the oven is evacuated for 30-60 minutes, in which the phase change materials can gradually penetrate into the pores of PMH. Finally, the excess phase change material is removed with filter paper, and the sample is cooled to obtain a phase change composite material. According to the different encapsulated phase change materials, they are recorded as PW@PMH, SA@PMH, LA@PMH, and MA@PMH respectively.

[0047] The present invention also includes the application of the phase change composite material in solar energy collection, heating, air conditioning, civil construction, and waste heat recovery.

[0048] For comparison, the same method S4 is used to encapsulate the phase change material in MH, which are denoted as PW@MH, SA@MH, LA@MH, and MA@MH, respectively, according to the different encapsulated phase change materials.

[0049] Results: Using HNT as raw material, a lightweight foamed geopolymer (MH) with rich pore structure was prepared by alkali excitation method and adding hollow glass microspheres. The calculated porosity was about 54-89%. PDMS was attached to the surface of MH by vapor deposition, and its contact angle changed from the original 0° to 153°-158.5°. It has a strong affinity with oily liquid phase change materials, and the encapsulation amount increased from the original 50-53% (encapsulated by MH) to 64-67% (encapsulated by PMH). The phase change material can still maintain its shape well at 80℃ without leakage. After 10 cycles of heating / cooling, the mass change of PMH phase change composite material is less than 2%, while the mass change of MH phase change composite material is greater than 30%, indicating that the superhydrophobic modification of PDMS can improve the thermal storage stability of phase change composite material. DSC test shows that PMH phase change composite material still maintains good latent heat after 1000 cycles of endothermic and exothermic cycles, further indicating that PMH phase change composite material has good stability. In addition, the superhydrophobic surface is moisture-proof and self-cleaning, can cope with various environments, and has broad application prospects.

[0050] Working principle:

[0051] In the present invention, super-hydrophobic modification of porous materials can effectively increase the packaging amount of phase change materials and reduce their leakage, and can avoid the degradation of thermal management performance due to moisture absorption in a humid environment. The super-hydrophobic property of the material also gives it a certain self-cleaning ability, which can be used for a long time in harsh environments.

[0052] The present invention uses halloysite as a raw material and hollow glass microspheres as a template to prepare a hierarchical porous foam geopolymer with high porosity through a chemical foaming method. After the hollow glass microspheres participate in the geopolymerization reaction, a hollow structure with the same diameter as the hollow glass microspheres is left. Therefore, by controlling the diameter and addition amount of the hollow glass microspheres, porous foam geopolymers with different pore structures can be obtained, thereby greatly improving the encapsulation amount of the phase change material. In addition, polydimethylsiloxane is deposited on the surface of the porous foam geopolymer by a vapor deposition method to obtain a super-hydrophobic porous geopolymer, which can improve the affinity of the porous geopolymer to the organic phase change material, is more conducive to encapsulating the phase change material in the pores, increases the encapsulation amount of the phase change material, and effectively improves its leakage problem.

[0053] The raw materials used in the present invention are cheap, easily available, and environmentally friendly; the preparation process is simple and energy-efficient. The surface of the modified halloysite geopolymer is transformed from hydrophilic to super-hydrophobic with a water contact angle greater than 150°. The super-hydrophobicity of the material can not only effectively increase the encapsulation amount of organic phase change materials and improve their leakage problems, but also avoid moisture absorption of the material, and has a certain self-cleaning ability, and can cope with various harsh application environments.

[0054] The working principle of the present invention:

[0055] The MH porous foam geopolymer obtained by the present invention is obtained by room temperature inorganic polymerization reaction using a mixed solution of NaOH and water glass as an alkali activator, H2O2 as a foaming agent, and hollow glass microspheres as a template. First, MHNT and hollow glass microspheres are added to the alkali activator, and the raw materials are decomposed into SiO4 tetrahedron and AlO4 tetrahedron structures under the action of strong alkali. These monomer structures share an oxygen atom to form polymer monomers, and then polymerize in the same way to form a three-dimensional network structure. The main chemical composition of the hollow glass microsphere is SiO2, which is also decomposed into SiO4 tetrahedron under the action of the alkali activator, and then participates in the reaction of the geopolymer, leaving spherical pores inside the geopolymer. Then, H2O2 and a surfactant are added to the geopolymer slurry and transferred to a specific mold. Since the geopolymer slurry is a strong alkali environment, H2O2 will quickly decompose and produce O2 to foam the slurry, generating a large number of holes, and the action of the surfactant will make these holes more uniform. Finally, the super-hydrophobic modification of MH is achieved by vapor deposition of PDMS. MH was mixed with PDMS and calcined in Ar gas. PDMS became gas phase at high temperature and deposited on the surface of the sample to obtain PDMS-modified MH foam geopolymer PMH.

[0056] Compared with the prior art, the present invention has the following beneficial effects:

[0057] 1. The present invention adopts the alkali excitation method to prepare porous foam geopolymer, and the reaction process is simple and easy to control. In addition, there are no by-products in the reaction process, which is environmentally friendly and pollution-free, and can be prepared in large quantities, which is convenient for production;

[0058] 2. The existing technology mentions the method of encapsulating phase change materials through geopolymers, and the encapsulation amount is basically 10-20%. However, this method uses hollow glass microspheres and H2O2 foaming to produce a multi-level pore structure, and the encapsulation amount can reach 50-53%, which greatly improves the encapsulation amount of phase change materials;

[0059] 3. Compared with MH without superhydrophobic modification, the encapsulation amount of PMH on phase change materials increased from 50-53% to 64-67%; in addition, PMH material showed excellent anti-leakage ability. After 10 thermal cycle tests at 80°C, the weight loss was less than 2%, while the leakage of samples without superhydrophobic modification was greater than 30%, indicating that the adsorption of phase change materials by superhydrophobic modification was significantly enhanced;

[0060] 4. Compared with the MH phase change composite material without superhydrophobic modification, the melting latent heat of the modified PMH phase change composite material increased by 14.2-16.4%, which further shows that the PMH after superhydrophobic modification can encapsulate more phase change materials and the thermal performance has been significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 The physical picture and self-cleaning test picture of PMH1 obtained in Example 1 of the present invention;

[0062] Figure 2 This is a SEM image of PMH1 obtained in Example 1 of the present invention;

[0063] Figure 3 XRD patterns of MHNT, MH1, PMH1, PW, and PW@PMH1 in Example 1 of the present invention; and FTIR patterns of MH1, PMH1, PW, PDMS, and PW@PMH1;

[0064] Figure 4 The leakage test diagrams of PW, PW@PMH1 in Example 1 of the present invention and PW@MH1 in Comparative Example 1; the mass change diagram of the internal paraffin of PW@MH1 and PW@PMH1 after 10 heat absorption and release cycles; the oil absorption comparison diagram of MH1 and PMH1;

[0065] Figure 5 TGA and DTA diagrams of MH1, PMH1, PW, and PW@PMH1 in Example 1 of the present invention;

[0066] Figure 6 DSC graphs of PW, PW@PMH1 in Example 1 of the present invention and PW@MH1 in Comparative Example 1; DSC graphs of PW@PMH1 and PW@PMH1(cycle); XRD graphs of PW@PMH1 and PW@PMH1(cycle); and FTIR graphs of PW@PMH1 and PW@PMH1(cycle).

[0067] Figure 7 XRD and FTIR diagrams of PMH5, SA, and SA@PMH5 in Example 5 of the present invention;

[0068] Figure 8 Leakage test diagrams of pure SA (Pure SA) of the present invention, SA@PMH5 in Example 5, and SA@MH5 in Comparative Example 2;

[0069] Fig. 9 1 is a cyclic temperature test diagram of SA@PMH5 in Example 5 of the present invention and SA@MH5 in Comparative Example 2;

[0070] Fig.10 DSC curves of SA, SA@PMH5 in Example 5 of the present invention and SA@MH5 in Comparative Example 2;

[0071] Fig.11 This is a water contact angle diagram of PMH6 obtained in Example 6 of the present invention;

[0072] Fig.12 This is a water contact angle diagram of PMH7 obtained in Example 7 of the present invention;

[0073] Fig.13 This is a water contact angle diagram of PMH8 obtained in Example 8 of the present invention;

[0074] Fig.14 It is a schematic diagram of the application of the PMH phase change composite material of the present invention. DETAILED DESCRIPTION

[0075] The present invention is further described below with reference to specific embodiments. The illustrative embodiments and descriptions of the present invention are used to explain the present invention but are not intended to limit the present invention.

[0076] All raw materials of the present invention are not particularly limited in their sources and are purchased from the market or prepared according to conventional methods well known to those skilled in the art.

[0077] The devices involved in the present invention are not particularly limited to devices commonly used in the art, and those skilled in the art are familiar with their operation and use methods.

[0078] The present invention is further described below with reference to specific embodiments. The illustrative embodiments and descriptions of the present invention are used to explain the present invention but are not intended to limit the present invention.

[0079] In the following embodiments, the hollow glass microspheres are soda lime borosilicate glass microspheres with a diameter of 20-75 μm.

[0080] Example 1

[0081] The method for preparing porous geopolymer comprises the following steps:

[0082] 1) Preparation of MHNT: HNT was calcined at 750° C. in an air atmosphere to dehydroxylate the HNT and obtain MHNT.

[0083] 2) Preparation of alkaline activator: Sodium hydroxide, water glass and water were mixed in a ratio (molar ratio) of SiO2:Na2O:H2O=1.38:1:15.74, and then stirred for 8 hours until the solution became clear and transparent to obtain an alkaline activator.

[0084] 3) Preparation of MH: MHNT and hollow glass microspheres were dispersed in the above-mentioned alkaline activator at a mass ratio of 2:1, the mass volume ratio of the solid raw material to the alkaline activator was 1:1.5, and the unit of mass volume ratio was g:mL; then 0.25% of the total mass of the solid material was added as a non-ionic surfactant F108 and 5% H2O2 aqueous solution (concentration of 30wt%) of the total mass of solid materials. Then, the above mixture was stirred with a glass rod until it was evenly mixed to obtain MHNT-based geopolymer slurry, which was then poured into a cylindrical silica gel mold (diameter × height = 30mm × 15mm) and covered with plastic wrap to prevent water evaporation. The sample was placed at room temperature for 10h to completely bubble and expand, and then transferred to a 60°C oven for rapid curing. After curing, the sample was removed from the mold and excess alkali in the sample was neutralized with an excess of 1M hydrochloric acid solution. Subsequently, the sample was washed several times with deionized water and dried overnight to obtain a MHNT-based porous foam geopolymer, recorded as MH1.

[0085] 4) Soak the dried MH1 in excess PDMS to make it fully contact with PDMS, and then place the sample in a heating and cooling state at a rate of 5°C min -1 The superhydrophobic porous geopolymer was finally obtained and recorded as PMH1.

[0086] The preparation method of the phase change composite material comprises the following steps:

[0087] PW was embedded in PMH1 by vacuum impregnation under the action of capillary attraction, surface tension, diffusion and adsorption. Specifically, excess PW and the prepared PMH1 geopolymer were placed in a glass beaker and placed in a vacuum oven at a temperature higher than the melting temperature of PW. After all PW was completely melted, the oven was evacuated for 1 h, in which PW could gradually penetrate into the pores of PMH1 porous geopolymer. Finally, the excess PW was sucked off with filter paper, and the sample was cooled to obtain the PW@PMH1 phase change composite.

[0088] The thermal storage performance test process of phase change composite materials is as follows:

[0089] 1) Leakage test: The PW@PMH1 composite material was heated at 40°C, 60°C and 80°C for 10 min, and the leakage of the material was determined by observing the phase change material remaining on the filter paper.

[0090] 2) Cyclic stability performance test: The PW@PMH1 composite material was heated at 80°C for 30 min, and then the mass change of PW was calculated by weighing. This process was repeated 10 times.

[0091] Comparative Example 1

[0092] The MH1 prepared in step 3) of Example 1 is encapsulated with the phase change material PW according to the steps of the preparation method of the phase change composite material in Example 1 to obtain PW@MH1.

[0093] like Figure 1As shown, Figure 1 The actual image of PMH1 obtained in Example 1 of the present invention and the self-cleaning test image are shown. The PMH1 sample has a porous structure and a calculated density of about 0.3 gm -2 , the porosity is about 71.49%. By immersing it in 20 mg L -1 The self-cleaning test was carried out in a methylene blue solution. Due to the superhydrophobic property of PMH1, the PMH1 sample will not be contaminated even if it is completely immersed in the dye.

[0094] The PMH1 of Example 1 was subjected to SEM test, and the test results are as follows: Figure 2 As shown, a hierarchical three-dimensional porous structure with three types of pores evenly distributed can be clearly observed. Specifically, the oxygen bubbles in the geopolymer slurry generated by the decomposition of hydrogen peroxide formed large pores with a diameter of 112-242μm (average 118.47μm). The intermediate pores (spherical voids with a diameter close to that of hollow glass balls) inside the porous geopolymer skeleton of PMH1 are formed by hollow glass balls. The main component on the hollow glass ball shell is silica, which can participate in the geopolymerization reaction, leaving hollow spherical holes on the PMH1 skeleton, further enriching the pore structure inside PMH1 and increasing the encapsulation amount of the phase change material. There are also a large number of small pores (average diameter 76.13nm), which are generated by the destruction of the tubular structure of MHNT and the occurrence of geopolymerization reaction. The hierarchical three-dimensional porous structure with rich pores provides a huge space for the encapsulation of phase change materials, thereby ensuring its encapsulation amount.

[0095] XRD and / or FTIR tests were performed on MH1, PMH1, PW@PMH1, MHNT, PDMS, and PW in Example 1. The results are as follows: Figure 3 As shown. Figure 3 As observed in a, the MH1 foam geopolymer is amorphous with a 2θ of 26.8°. The reflections are broader when MgNT is reacted with alkaline solution and move to higher angle regions after reaction. This is due to the incorporation of smaller radius atoms in the alkaline activator into the host. In addition, the quartz peak at 23.7° increases slightly, which is caused by the connection of silicon material to the geopolymer matrix, indicating that the network of the geopolymer is reorganized and formed. After modification with PDMS, the amorphous peak of the geopolymer does not change, indicating that the deposition of PDMS maintains the structural integrity of the geopolymer. The new peaks that appeared confirmed the deposition of PDMS on the surface of MH1 foam geopolymer. Figure 3As shown in (b), no characteristic peaks of PMH1 were detected, while the characteristic peaks of pure PW were clearly visible, indicating that PMH1 has good compatibility with PW, high encapsulation ability, and the crystal structure of PW remains unchanged after encapsulation. Compared with pure PW, PW@PMH1 shows almost the same peak position and intensity, which indicates that no new crystalline phase is generated. In addition, since the encapsulation amount of PW in PMH1 is very high, the characteristic peaks of PMH1 are not observed. FTIR was used to observe the changes in functional groups in the samples ( Figure 3 c, Figure 3 d). The peak position of PMH1 is basically consistent with that of MH1 foam geopolymer and PDMS, which proves that PDMS is successfully loaded on MH1 and PDMS does not decompose under high temperature conditions ( Figure 3 c) If Figure 3 As shown in c, both MH1 and PMH1 have typical geopolymer structures, with the peaks at 3416, 1641, 1422, and 1000 cm -1 The absorption bands of PMH1 are the stretching vibration of OH on the surface, the bending vibration of embedded water molecules, the stretching vibration of carbonates, and the stretching vibration of Si-O-Si or Al-O-Si bonds. However, compared with MH1, PMH1 has a weaker absorption band in the range of 2905-2965cm -1 This corresponds to the CH stretching of -CH3 and -CH2 in PDMS, which is consistent with the XRD results, further confirming the successful modification of MH1 by PDMS. Figure 3 d is the FTIR spectra of pure PW, PMH1 and PW@PMH1. In pure PW, 2916 cm -1 and 2847cm -1 The symmetrical stretching vibration peaks of -CH3 and -CH2 are 1461 cm -1 It is the deformation vibration peak of -CH3 and -CH2, 728cm -1 The peaks are the plane swing peaks of -CH3 and -CH2. After PW was encapsulated in PMH1 foam geopolymer, the peaks of pure PW were still clearly observed, while the peaks of PMH1 were slightly reduced in PW@PMH1, indicating that the chemical properties of PW remained unchanged and the encapsulated paraffin weakened the characteristic peaks of PMH1.

[0096] Figure 4 The leakage test diagram of PW, PW@PMH1 in Example 1 of the present invention and PW@MH1 in Comparative Example 1; the mass change diagram of the internal paraffin of PW@MH1 and PW@PMH1 after 10 heat absorption and release cycles; and the oil absorption comparison diagram of MH1 and PMH1. Figure 4a, All samples remained in a solid cylindrical shape for 10 min at 40 °C without any leakage on the filter paper, which is due to the melting temperature of PW being higher than 40 °C. When the temperature was increased to 60 °C, pure PW began to melt immediately, but the leakage was not obvious, and little liquid was left on the filter paper, while no leakage was found in PW@MH1 and PW@PMH1. However, when the temperature was further increased to 80 °C, PW leaked significantly after 2 min, and PW melted more after 10 min. In contrast, the PW@MH1 and PW@PMH1 composites remained in a basically solid cylindrical shape after heating at 80 °C for 10 min. PW@PMH1 did not have any leakage, while PW@MH1 leaked after heating at 80 °C for 10 min. These results indicate that the obtained PW@MH1 and PW@PMH1 have better shape stability and leakage resistance than pure PW, which is due to the hierarchical three-dimensional porous structure of the geopolymer that can hold and fix the melted PW under the action of capillary force and surface tension. At the same time, the strong chemical affinity between PW and PDMS in PW@PMH1 is conducive to improving the fixation ability of PMH to the phase change material, thereby greatly reducing the occurrence of leakage. In order to further study the anti-leakage ability of the obtained phase change composite material, PW@MH1 and PW@PMH1 were heated at 80 °C for 30 min for a total of 10 cycles ( Figure 4 b). Obviously, PW@PMH1 can still retain more than 98wt% of the mass of PW after 10 cycles, while PW in PW@MH1 only retains less than 70wt%, further confirming that PW@PMH1 has better anti-leakage performance than PW@MH1. Due to the abundant pores in MH1, when the capillary force and surface tension are not enough to accommodate the pores, the liquid PW will flow out of the pores. However, the PDMS on PMH1 has a strong chemical affinity for oily liquid PW, thereby reducing the leakage phenomenon. By further comparing the absorption rate of PMH1 and MH1 for plant oil ( Figure 4 c), it can be seen that for the superhydrophobic PMH1, the oil droplet is completely absorbed into the interior within 70 seconds, while for the unmodified MH1, the oil droplet stays on its surface for 480 seconds before being completely absorbed. The surface superhydrophobic modification increases the affinity of the material for oily liquids and helps the encapsulation of oily phase change materials.

[0097] The thermal stability of MH1, PMH1, PW, and PW@PMH1 obtained in Example 1 was determined by TGA and DTG. Figure 5As shown in the figure, the weight loss of MH1 porous foam geopolymer below 800℃ is negligible (2.04%), which mainly corresponds to the internal residual water, indicating its good thermal stability and ensuring its practical application in thermal storage. Among them, the weight loss below 300℃ is 1.5%, which is mainly due to the evaporation of physical structural water in the small pore structure, while the weight loss above 300℃ is 0.54%, which is mainly caused by the dihydroxylation of chemically bound water. For pure paraffin, there is almost no weight change (<1%) before 200℃, which shows that paraffin is thermally stable within the temperature range of its solid-liquid phase change, providing advantages in thermal storage applications. When the temperature rises to 260℃, paraffin begins to decompose and the mass decreases by about 3%, and then rapidly decreases. Compared with MH1, the weight loss of PMH1 increases to 4.27%, indicating that PDMS is thermally decomposed into volatile organic compounds such as silane and ethane. Assuming that all PDMS can be decomposed at 800℃, the PDMS on MH1 can be roughly estimated to be 2.23%. After encapsulating PW in PMH1, the weight loss of PW@PMH1 can be significantly increased to 69.90%, of which 2.15% weight loss below 260°C is due to physical evaporation of PDMS, and a significant weight loss of 67% between 300-400°C corresponds to the thermal decomposition of PW into volatile gases, liquid hydrocarbons and solid carbon black. According to TGA, the PW encapsulated in PMH1 is estimated to be 67%, which is very close to the porosity of PMH1 mentioned above, indicating that almost all pores in PMH1 are filled with PW. The change in the decomposition rate of the sample can be more directly observed from the DTG curve. It can be seen that PW@PMH1 and pure PW have similar initial decomposition temperatures of about 210°C. The peak and end points of the decomposition rate of PW@PMH1 are higher than those of pure PW, indicating that the encapsulation effect of PMH1 improves the thermal stability of PW.

[0098] The phase transition characteristics of pure PW, PW@PMH1 in Example 1 and PW@MH1 in Comparative Example 1 were studied by DSC, and the melting temperature (T m ), melting enthalpy (ΔH m ), solidification temperature (T f ) and solidification enthalpy (ΔH f )(Table 1). The results are as follows Figure 6 As shown in Table 1, PW@MH1 and PW@PMH1 exhibit similar heating / cooling characteristics to pure PW (T m / T f ), indicating that the physical properties of PW remain unchanged after being encapsulated by MH1 and PMH1. Figure 6 a and Table 1 show that the ΔH of pure PW m / ΔH f The value is 195.0 / 189.9 J g -1 , while the ΔH of PW@MH1 and PW@PMH1 compositesm / ΔH f The values ​​dropped to 112.6 / 105.9 and 131.1 / 121.8 J g -1 , indicating that part of the latent heat is lost because the porous geopolymers MH1 and PMH1 have no heat storage properties. The encapsulation efficiency can be calculated based on Calculate, where E is the packaging efficiency, ΔH m is the melting enthalpy of the phase change composite material, ΔH m ' is the melting enthalpy of pure phase change material. The results show that the encapsulation efficiency of PW@PMH1 is 67.23% and that of PW@MH1 is 57.74%, which is similar to the encapsulation rate calculated from the weight difference of geopolymer and composite material, indicating that the heat storage performance of PW is not affected by MH1 or PMH1, and PMH1 and PW are more compatible. PW@PMH1 was repeatedly heated and cooled for 1000 cycles by DSC to test its thermal repeatability and chemical stability ( Figure 6 b) If Figure 6 As shown in (b), the endothermic and exothermic curves of PW@PMH1 before and after 1000 cycles are consistent, and the peak value and intensity are almost the same, indicating its excellent phase change reversibility, recoverability and repeatability. m , ΔH f , T m , T f The fluctuation rates were as low as 3.28%, 0.22%, 0.03%, and 3.27%, respectively, and the latent heat was reduced by only 3.27% (Table 1), which is within an acceptable fluctuation range in practical applications. The thermal and chemical stability of the samples after cycling were tested by XRD and FTIR ( Figure 6 c, 6d). Similarly, PW@PMH1 showed almost similar shapes and characteristic peaks before and after XRD and FTIR cycles, indicating that it has good crystal structure and chemical stability. These results indicate that the PW@PMH1 composite has good thermal stability, which is due to the strong chemical affinity, capillary force and surface tension between PMH1 and PW.

[0099] Example 2

[0100] The difference between this embodiment and embodiment 1 is that in the preparation process of geopolymer, a mass ratio of MHNT and hollow glass microspheres of 4:1 is used instead of the raw material ratio of 2:1 in step 2) of embodiment 1, and the other synthesis steps are the same as in embodiment 1.

[0101] The specific steps are: MHNT (prepared in Example 1) and hollow glass microspheres are dispersed in the above-mentioned alkali activator (prepared in Example 1) at a mass ratio of 4:1, the mass volume ratio of the solid raw material to the alkali activator is 1:1.5, and the unit of the mass volume ratio is g:mL; then 0.25% of the total mass of the solid material is added with a non-ionic surfactant F108 and 5% of the total mass of solid materials in a 30wt% H2O2 aqueous solution. Next, the mixture was stirred with a glass rod until well mixed to obtain a MHNT-based geopolymer slurry, which was then poured into a cylindrical silica gel mold (diameter × height = 30mm × 15mm) and covered with plastic wrap to prevent water evaporation. The sample was left at room temperature to fully bubble and expand, and then transferred to a 60°C oven for rapid curing. After curing, the sample was removed from the mold and the sample was neutralized with an excess of 1M hydrochloric acid solution to remove excess alkali. Subsequently, the sample was washed several times with deionized water and dried overnight to obtain a MHNT-based porous foam geopolymer, recorded as MH2.

[0102] The dried MH2 was immersed in excess PDMS to make it fully contact with PDMS, and then the sample was placed in a heating and cooling state with a rate of 5 °C min -1 The samples were placed in a tube furnace and heated at 300 °C in an Ar gas environment and were denoted as PMH2.

[0103] The preparation method of the phase change composite material comprises the following steps:

[0104] PW was embedded in PMH2 by vacuum impregnation under the action of capillary attraction, surface tension, diffusion and adsorption. Specifically, excess PW and the prepared PMH2 geopolymer were placed in a glass beaker and put into a vacuum oven with a temperature higher than the melting temperature of PW. After all PW was completely melted, the oven was evacuated for 1 h, in which PW could gradually penetrate into the pores of PMH2 foam geopolymer. Finally, the excess PW was removed with filter paper, and the sample was cooled to obtain the PW@PMH2 composite material.

[0105] The phase change composite material obtained in this example was tested using the same leakage test and cycle stability performance test as in Example 1.

[0106] Example 3

[0107] The difference between this embodiment and embodiment 1 is that in the preparation process of geopolymer, a mass ratio of MHNT and hollow glass microspheres of 3:1 is used instead of the raw material ratio of 2:1 in step 2) of embodiment 1, and the other synthesis steps are the same as in embodiment 1.

[0108] The specific steps are: MHNT (prepared in Example 1) and hollow glass microspheres are dispersed in the above-mentioned alkali activator (prepared in Example 1) at a mass ratio of 3:1, the mass volume ratio of the solid raw material to the alkali activator is 1:1.5, and the unit of the mass volume ratio is g:mL; then 0.25% of the total mass of the solid material is added with a non-ionic surfactant F108 and 5% of the total mass of solid materials in a 30wt% H2O2 aqueous solution. Next, the mixture was stirred with a glass rod until it was evenly mixed to obtain a MHNT-based geopolymer slurry, which was then poured into a cylindrical silica gel mold (diameter × height = 30mm × 15mm) and covered with plastic wrap to prevent water evaporation. The sample was left at room temperature to fully bubble and expand, and then transferred to a 60°C oven for rapid curing. After curing, the sample was removed from the mold and the sample was neutralized with an excess of 1M hydrochloric acid solution to remove excess alkali. Subsequently, the sample was washed several times with deionized water and dried overnight to obtain a MHNT-based porous foam geopolymer, recorded as MH3.

[0109] The dried MH3 was immersed in excess PDMS to make it fully contact with PDMS, and then the sample was placed in a heating and cooling state with a rate of 5 °C min -1 The samples were placed in a tube furnace and heated at 300 °C in an Ar gas environment and were denoted as PMH3.

[0110] The preparation method of the phase change composite material comprises the following steps:

[0111] PW was embedded in PMH3 by vacuum impregnation under the action of capillary attraction, surface tension, diffusion and adsorption. Specifically, excess PW and the prepared PMH3 geopolymer were placed in a glass beaker and put into a vacuum oven with a temperature higher than the melting temperature of PW. After all PW was completely melted, the oven was evacuated for 1 h, in which PW could gradually penetrate into the pores of PMH3 foam geopolymer. Finally, the excess PW was removed with filter paper, and the sample was cooled to obtain the PW@PMH3 composite material.

[0112] The phase change composite material obtained in this example was tested using the same leakage test and cycle stability performance test as in Example 1.

[0113] Example 4

[0114] The difference between this embodiment and embodiment 1 is that in the preparation process of the porous geopolymer, a mass ratio of 1:1 between MHNT and hollow glass microspheres is used instead of the raw material ratio of 2:1 in step 2) of embodiment 1, and the other synthesis steps are the same as those in embodiment 1.

[0115] The specific steps are: dispersing MHNT (prepared in Example 1) and hollow glass microspheres in the above-mentioned alkali activator (prepared in Example 1) at a mass ratio of 1:1, the mass volume ratio of the solid raw material to the alkali activator is 1:1.5, and the unit of the mass volume ratio is g:mL; then adding 0.25% of the total mass of the solid material non-ionic surfactant F108 and 5% of the total mass of solid materials in a 30wt% H2O2 aqueous solution. Next, the mixture was stirred with a glass rod until mixed evenly to obtain a MHNT-based geopolymer slurry, which was then poured into a cylindrical silica gel mold (diameter × height = 30mm × 15mm) and covered with plastic wrap to prevent water evaporation. The sample was left at room temperature to fully bubble and expand, and then transferred to a 60°C oven for rapid curing. After curing, the sample was removed from the mold and the sample was neutralized with an excess of 1M hydrochloric acid solution to remove excess alkali. Subsequently, the sample was washed several times with deionized water and dried overnight to obtain a MHNT-based porous foam geopolymer, recorded as MH4.

[0116] The dried MH4 was immersed in PDMS to make it fully contact with PDMS, and then the sample was placed in a heating and cooling state with a rate of 5 °C min -1 The sample was placed in a tube furnace and heated at 300 °C in an Ar gas environment and was denoted as PMH4.

[0117] The preparation method of the phase change composite material comprises the following steps:

[0118] PW was embedded in PMH4 by vacuum impregnation under the action of capillary attraction, surface tension, diffusion and adsorption. Specifically, excess PW and the prepared PMH4 geopolymer were placed in a glass beaker and put into a vacuum oven with a temperature higher than the melting temperature of PW. After all PW was completely melted, the oven was evacuated for 1 h, in which PW could gradually penetrate into the pores of PMH4 foam geopolymer. Finally, the excess PW was removed with filter paper, and the sample was cooled to obtain the PW@PMH4 composite material.

[0119] The phase change composite material obtained in this example was tested using the same leakage test and cycle stability performance test as in Example 1.

[0120] Example 5

[0121] The difference between this embodiment and embodiment 1 is that in the preparation process of the phase change composite material, stearic acid (SA) is used instead of PW as the phase change material, and the other synthesis steps are the same as those in embodiment 1.

[0122] The specific steps are as follows: MHNT (prepared in Example 1) and hollow glass microspheres are dispersed in the above-mentioned alkali activator (prepared in Example 1) at a mass ratio of 2:1, the mass volume ratio of the solid raw material to the alkali activator is 1:1.5, and the unit of the mass volume ratio is g:mL; then 0.25% of the total mass of the solid material is added as a non-ionic surfactant F108 and 5% of the total mass of solid materials in a 30wt% H2O2 aqueous solution. Next, the mixture was stirred with a glass rod until well mixed to obtain an MHNT-based geopolymer slurry, which was then poured into a cylindrical silica gel mold (diameter × height = 30mm × 15mm) and covered with plastic wrap to prevent water evaporation. The sample was left at room temperature to fully bubble and expand, and then transferred to a 60°C oven for rapid curing. After curing, the sample was removed from the mold and the sample was neutralized with an excess of 1M hydrochloric acid solution to remove excess alkali. Subsequently, the sample was washed several times with deionized water and dried overnight to obtain an MHNT-based porous foam geopolymer, recorded as MH5.

[0123] The dried MH5 was immersed in excess PDMS to make it fully contact with PDMS, and then the sample was placed in a heating and cooling state with a rate of 5 °C min -1 The sample was placed in a tube furnace and heated at 300 °C in an Ar gas environment and was denoted as PMH5.

[0124] The preparation method of the phase change composite material comprises the following steps:

[0125] SA was embedded in PMH5 by vacuum impregnation under the action of capillary attraction, surface tension, diffusion and adsorption. Specifically, excess SA and the prepared PMH5 geopolymer were placed in a glass beaker and placed in a vacuum oven at a temperature higher than the melting temperature of SA. After all SA was completely melted, the oven was evacuated for 1 h, in which SA could gradually penetrate into the pores of PMH5 foam geopolymer. Finally, the excess SA was removed with filter paper, and the sample was cooled to obtain the SA@PMH5 composite material.

[0126] The phase change composite material obtained in this example was tested using the same leakage test and cycle stability performance test as in Example 1.

[0127] Comparative Example 2

[0128] The MH5 prepared in Example 5 is encapsulated with the phase change material SA according to the steps of the preparation method of the phase change composite material in Example 5 to obtain SA@MH5.

[0129] Table 1 Enthalpy changes of relevant samples in Example 1, Example 5, Comparative Example 1 and Comparative Example 2

[0130]

[0131]

[0132] In the above table, PW@PMH1(cycle) refers to the phase change composite material obtained by repeatedly heating and cooling PW@PMH1 for 1000 cycles using DSC; SA@PMH5(cycle) refers to the phase change composite material obtained by repeatedly heating and cooling SA@PMH5 for 1000 cycles using DSC.

[0133] XRD and FTIR tests were performed on PMH5, SA, and SA@PMH5 in Example 5. The results are as follows: Figure 7 As shown in the figure, after SA was encapsulated by PMH5 foam geopolymer, no characteristic peaks of PMH5 were detected, while the characteristic peaks of pure SA were clearly visible, indicating that PMH5 has good compatibility with SA, high encapsulation ability, and the crystal structure of SA remains unchanged after encapsulation. Compared with pure SA, SA@PMH5 showed almost the same peak position and intensity, which indicated that no new crystalline phase was generated and the encapsulation amount of SA in PMH5 was very high. After encapsulation by PMH5 foam geopolymer, the peaks of pure SA were still clearly observed, while the peaks of PMH5 were slightly reduced in PW@PMH5, verifying that the chemical properties of SA remained unchanged and that the characteristic peaks of PMH5 were covered after encapsulation of SA.

[0134] Pure SA, SA@PMH5 obtained in Example 5, and SA@MH5 in Comparative Example 2 were subjected to leakage tests, and the results are shown in Figure 8. Pure SA, SA@MH5, and SA@PMH5 were heated at 80°C for 10 min, and the SA residue on the filter paper was observed. Pure SA completely melted after heating because it did not have shape stability; MH5 did not have a strong affinity with the phase change material, so SA@MH5 left a small amount of residue after heating; PMH5 had a strong affinity with the phase change material, so no leakage residue was observed for SA@PMH5 after heating.

[0135] The SA@PMH5 obtained in Example 5 and the SA@MH5 in Comparative Example 2 were subjected to a cyclic comparison. SA@MH5 and SA@PMH5 were heated at 80°C for 30 minutes for a total of 10 cycles. The results are as follows: Fig. 9 As shown. Obviously, SA@PMH5 can still retain about 99wt% of SA after 10 cycles, while less than 77wt% of SA is retained in SA@MH5, further confirming that SA@PMH5 has better anti-leakage performance than SA@MH5. Due to the abundant pores in MH5, liquid SA will flow out of the pores when the capillary force and surface tension are not enough to accommodate the pores. However, PDMS on PMH5 has a strong chemical affinity for oily liquid SA, which reduces the leakage phenomenon.

[0136] DSC tests were performed on SA, SA@PMH5 obtained in Example 5, and SA@MH5 in Comparative Example 2. The results are as follows: Fig.10 As shown in the figure, it can be observed that SA@MH5 and SA@PMH5 exhibit similar heating / cooling characteristics (T m / T f ), indicating that the physical properties of SA remain unchanged after being encapsulated by MH5 and PMH5. In addition, SA@MH5 exhibits a smaller peak than SA@PMH5, which is due to the lower encapsulation amount of SA@MH5 and a large amount of SA leakage during the heating process.

[0137] Example 6

[0138] The difference between this embodiment and embodiment 1 is that a heating temperature of 350° C. is used in the superhydrophobic modification process of the geopolymer (step 4), and the other synthesis steps are the same as those in embodiment 1.

[0139] The specific steps are as follows: MHNT (prepared in Example 1) and hollow glass microspheres are dispersed in the above-mentioned alkali activator (prepared in Example 1) at a mass ratio of 2:1, the mass volume ratio of the solid raw material to the alkali activator is 1:1.5, and the unit of the mass volume ratio is g:mL; then 0.25% of the total mass of the solid material is added as a non-ionic surfactant F108 and 5% of the total mass of solid materials in a 30wt% H2O2 aqueous solution. Next, the mixture was stirred with a glass rod until well mixed to obtain a MHNT-based geopolymer slurry, which was then poured into a cylindrical silica gel mold (diameter × height = 30mm × 15mm) and covered with plastic wrap to prevent water evaporation. The sample was left at room temperature to fully bubble and expand, and then transferred to a 60°C oven for rapid curing. After curing, the sample was removed from the mold and the sample was neutralized with an excess of 1M hydrochloric acid solution to remove excess alkali. Subsequently, the sample was washed several times with deionized water and dried overnight to obtain a MHNT-based porous foam geopolymer, recorded as MH6.

[0140] The dried MH6 was immersed in excess PDMS to make it fully contact with PDMS, and then the sample was placed in a heating and cooling state with a rate of 5 °C min -1 The sample was placed in a tube furnace and heated at 350 °C in an Ar gas environment and was denoted as PMH6.

[0141] The preparation method of the phase change composite material comprises the following steps:

[0142] PW was embedded in PMH6 by vacuum impregnation under the action of capillary attraction, surface tension, diffusion and adsorption. Specifically, excess PW and the prepared PMH6 geopolymer were placed in a glass beaker and put into a vacuum oven with a temperature higher than the melting temperature of PW. After all PW was completely melted, the oven was evacuated for 1 h, in which PW could gradually penetrate into the pores of PMH6 foam geopolymer. Finally, the excess PW was removed with filter paper, and the sample was cooled to obtain the PW@PMH6 composite material.

[0143] The water contact angle test of PMH6 obtained in Example 6 was performed, and the results were as follows: Fig.11 As shown, it can be seen that the sample modified at 350°C exhibits a water contact angle of 153.9±0.1°.

[0144] Example 7

[0145] The difference between this embodiment and embodiment 1 is that a heating temperature of 400° C. is used in the superhydrophobic modification process of the geopolymer (step 4), and the other synthesis steps are the same as those in embodiment 1.

[0146] The specific steps are as follows: MHNT (prepared in Example 1) and hollow glass microspheres are dispersed in the above-mentioned alkali activator (prepared in Example 1) at a mass ratio of 2:1, the mass volume ratio of the solid raw material to the alkali activator is 1:1.5, and the unit of the mass volume ratio is g:mL; then 0.25% of the total mass of the solid material is added as a non-ionic surfactant F108 and 5% of the total mass of solid materials in a 30wt% H2O2 aqueous solution. Next, the mixture was stirred with a glass rod until it was evenly mixed to obtain a MHNT-based geopolymer slurry, which was then poured into a cylindrical silica gel mold (diameter × height = 30mm × 15mm) and covered with plastic wrap to prevent water evaporation. The sample was left at room temperature to fully bubble and expand, and then transferred to a 60°C oven for rapid curing. After curing, the sample was removed from the mold and the sample was neutralized with an excess of 1M hydrochloric acid solution to remove excess alkali. Subsequently, the sample was washed several times with deionized water and dried overnight to obtain a MHNT-based porous foam geopolymer, recorded as MH7.

[0147] The dried MH7 was immersed in excess PDMS to make it fully contact with PDMS, and then the sample was placed in a heating and cooling state with a rate of 5 °C min -1 The sample was placed in a tube furnace and heated at 400 °C in an Ar gas environment and was denoted as PMH7.

[0148] The preparation method of the phase change composite material comprises the following steps:

[0149] PW was embedded in PMH7 by vacuum impregnation under the action of capillary attraction, surface tension, diffusion and adsorption. Specifically, excess PW and the prepared PMH7 geopolymer were placed in a glass beaker and put into a vacuum oven with a temperature higher than the melting temperature of PW. After all PW was completely melted, the oven was evacuated for 1 h, in which PW could gradually penetrate into the pores of PMH7 foam geopolymer. Finally, the excess PW was removed with filter paper, and the sample was cooled to obtain the PW@PMH7 composite material.

[0150] The water contact angle test of PMH7 obtained in Example 7 was performed, and the results were as follows: Fig.12 It can be seen that the sample modified at 400 °C exhibits a water contact angle of 154.7 ± 0.1°.

[0151] Example 8

[0152] The difference between this embodiment and embodiment 1 is that a heating temperature of 450° C. is used in the superhydrophobic modification process of the geopolymer (step 4), and the other synthesis steps are the same as those in embodiment 1.

[0153] The specific steps are as follows: MHNT (prepared in Example 1) and hollow glass microspheres are dispersed in the above-mentioned alkali activator (prepared in Example 1) at a mass ratio of 2:1, the mass volume ratio of the solid raw material to the alkali activator is 1:1.5, and the unit of the mass volume ratio is g:mL; then 0.25% of the total mass of the solid material is added as a non-ionic surfactant F108 and 5% of the total mass of solid materials in a 30wt% H2O2 aqueous solution. Next, the mixture was stirred with a glass rod until it was evenly mixed to obtain an MHNT-based geopolymer slurry, which was then poured into a cylindrical silica gel mold (diameter × height = 30mm × 15mm) and covered with plastic wrap to prevent water evaporation. The sample was left at room temperature to fully bubble and expand, and then transferred to a 60°C oven for rapid curing. After curing, the sample was removed from the mold and the sample was neutralized with an excess of 1M hydrochloric acid solution to remove excess alkali. Subsequently, the sample was washed several times with deionized water and dried overnight to obtain an MHNT-based porous foam geopolymer, recorded as MH8.

[0154] The dried MH8 was immersed in excess PDMS to make it fully contact with PDMS, and then the sample was placed in a heating and cooling state with a rate of 5 °C min -1 The sample was placed in a tube furnace and heated at 450 °C in an Ar gas environment and was denoted as PMH8.

[0155] The preparation method of the phase change composite material comprises the following steps:

[0156] PW was embedded in PMH8 by vacuum impregnation under the action of capillary attraction, surface tension, diffusion and adsorption. Specifically, excess PW and the prepared PMH8 geopolymer were placed in a glass beaker and put into a vacuum oven with a temperature higher than the melting temperature of PW. After all PW was completely melted, the oven was evacuated for 1 h, in which PW could gradually penetrate into the pores of PMH8 foam geopolymer. Finally, the excess PW was removed with filter paper, and the sample was cooled to obtain the PW@PMH8 composite material.

[0157] The water contact angle test of PMH8 obtained in Example 8 was performed, and the results were as follows: Fig.13 It can be seen that the sample modified at 450°C exhibits a water contact angle of 158.5±0.1°.

[0158] Example 9

[0159] The difference between this embodiment and embodiment 1 is that lauric acid (LA) is used as the phase change material instead of PW in the preparation process of the phase change composite material, and the other synthesis steps are the same as those in embodiment 1.

[0160] The specific steps are as follows: MHNT (prepared in Example 1) and hollow glass microspheres are dispersed in the above-mentioned alkali activator (prepared in Example 1) at a mass ratio of 2:1, the mass volume ratio of the solid raw material to the alkali activator is 1:1.5, and the unit of the mass volume ratio is g:mL; then 0.25% of the total mass of the solid material is added as a non-ionic surfactant F108 and 5% of the total mass of solid materials in a 30wt% H2O2 aqueous solution. Next, the mixture was stirred with a glass rod until well mixed to obtain an MHNT-based geopolymer slurry, which was then poured into a cylindrical silica gel mold (diameter × height = 30 mm × 15 mm) and covered with plastic wrap to prevent water evaporation. The sample was left at room temperature to fully bubble and expand, and then transferred to a 60°C oven for rapid curing. After curing, the sample was removed from the mold and the sample was neutralized with an excess of 1M hydrochloric acid solution to remove excess alkali. Subsequently, the sample was washed several times with deionized water and dried overnight to obtain an MHNT-based porous foam geopolymer, recorded as MH9.

[0161] The dried MH9 was immersed in excess PDMS to make it fully contact with PDMS, and then the sample was placed in a heating and cooling state with a rate of 5 °C min -1 The sample was placed in a tube furnace and heated at 300 °C in an Ar gas environment and was denoted as PMH9.

[0162] The preparation method of the phase change composite material comprises the following steps:

[0163] LA was embedded in PMH9 by vacuum impregnation under the action of capillary attraction, surface tension, diffusion and adsorption. Specifically, excess LA and the prepared PMH8 geopolymer were placed in a glass beaker and placed in a vacuum oven at a temperature higher than the melting temperature of LA. After all LA was completely melted, the oven was evacuated for 1 h, in which LA could gradually penetrate into the pores of PMH9 foam geopolymer. Finally, the excess LA was removed with filter paper, and the sample was cooled to obtain the LA@PMH9 composite material.

[0164] The phase change composite material obtained in this example was tested using the same leakage test and cycle stability performance test as in Example 1.

[0165] Example 10

[0166] The difference between this embodiment and embodiment 1 is that in the preparation process of the phase change composite material, myristic acid (MA) is used instead of PW as the phase change material, and the other synthesis steps are the same as those in embodiment 1.

[0167] The specific steps are as follows: MHNT (prepared in Example 1) and hollow glass microspheres are dispersed in the above-mentioned alkali activator (prepared in Example 1) at a mass ratio of 2:1, the mass volume ratio of the solid raw material to the alkali activator is 1:1.5, and the unit of the mass volume ratio is g:mL; then 0.25% of the total mass of the solid material is added as a non-ionic surfactant F108 and 5% of the total mass of solid materials in a 30wt% H2O2 aqueous solution. Next, the mixture was stirred with a glass rod until well mixed to obtain an MHNT-based geopolymer slurry, which was then poured into a cylindrical silica gel mold (diameter × height = 30mm × 15mm) and covered with plastic wrap to prevent water evaporation. The sample was left at room temperature to completely bubble and expand, and then transferred to a 60°C oven for rapid curing. After curing, the sample was removed from the mold and the sample was neutralized with an excess of 1M hydrochloric acid solution to remove excess alkali. Subsequently, the sample was washed several times with deionized water and dried overnight to obtain an MHNT-based porous foam geopolymer, recorded as MH 10 .

[0168] The dried MH 10 The sample was immersed in excess PDMS to make full contact with PDMS, and then the sample was placed in a heating and cooling state with a rate of 5 °C min -1 The samples were placed in a tube furnace and heated at 300 °C in an Ar gas environment. 10 .

[0169] The preparation method of the phase change composite material comprises the following steps:

[0170] MA was embedded in PMH by vacuum impregnation under the action of capillary attraction, surface tension, diffusion and adsorption. 10 Specifically, excess MA and prepared PMH 10 The geopolymer was placed in a glass beaker and placed in a vacuum oven at a temperature higher than the melting temperature of the MA. After all the MA was completely melted, the oven was evacuated for 1 h, during which the MA could gradually penetrate into the PMH. 10 Finally, the excess MA was removed with filter paper and the sample was cooled to obtain MA@PMH. 10 Composite materials.

[0171] The phase change composite material obtained in this example was tested using the same leakage test and cycle stability performance test as in Example 1.

[0172] Embodiment 11

[0173] The difference between this embodiment and embodiment 1 is that a calcination temperature of 650° C. is used in the process of preparing the geopolymerization active metahaloysite (step 1). The other synthesis steps are the same as those in embodiment 1.

[0174] The specific steps are as follows: HNT is calcined at 650° C. in an air atmosphere to dehydroxylate it and obtain meta-haloysite (MHNT).

[0175] The MHNT and hollow glass microspheres are dispersed in the alkali activator (prepared in Example 1) at a mass ratio of 2:1, the mass volume ratio of the solid raw material to the alkali activator is 1:1.5, and the unit of the mass volume ratio is g:mL; then 0.25% of the total mass of the solid material is added with a nonionic surfactant F 108 and 5% of the total mass of solid materials in a 30wt% H2O2 aqueous solution. Next, the mixture was stirred with a glass rod until mixed evenly to obtain an MHNT-based geopolymer slurry, which was then poured into a cylindrical silica gel mold (diameter × height = 30 mm × 15 mm) and covered with plastic wrap to prevent water evaporation. The sample was left at room temperature to completely bubble and expand, and then transferred to a 60°C oven for rapid curing. After curing, the sample was removed from the mold and the sample was neutralized with an excess of 1M hydrochloric acid solution to remove excess alkali. Subsequently, the sample was washed several times with deionized water and dried overnight to obtain an MHNT-based porous foam geopolymer, recorded as MH 11 .

[0176] The dried MH 11 The sample was immersed in excess PDMS to make full contact with PDMS, and then the sample was placed in a heating and cooling state with a rate of 5 °C min -1The samples were placed in a tube furnace and heated at 300 °C in an Ar gas environment. 11 .

[0177] The preparation method of the phase change composite material comprises the following steps:

[0178] PW was embedded in PMH by vacuum impregnation under the action of capillary attraction, surface tension, diffusion and adsorption. 11 Specifically, excess PW and prepared PMH 11 The geopolymer was placed in a glass beaker and placed in a vacuum oven at a temperature higher than the melting temperature of PW. After all PW was completely melted, the oven was evacuated for 1 h, during which PW could gradually penetrate into PMH. 11 Finally, the excess PW was removed with filter paper and the sample was cooled to obtain PW@PMH 11 Composite materials.

[0179] The phase change composite material obtained in this example was tested using the same leakage test and cycle stability performance test as in Example 1.

[0180] Example 12

[0181] The difference between this embodiment and embodiment 1 is that a calcination temperature of 700° C. is used in the process of preparing the geopolymerization active metahaloysite (step 1). The other synthesis steps are the same as those in embodiment 1.

[0182] The specific steps are as follows: calcining HNT at 700° C. in an air atmosphere to dehydroxylate HNT and obtain meta-haloysite (MHNT).

[0183] The MHNT and hollow glass microspheres are dispersed in the alkali activator (prepared in Example 1) at a mass ratio of 2:1, the mass volume ratio of the solid raw material to the alkali activator is 1:1.5, and the unit of the mass volume ratio is g:mL; then 0.25% of the total mass of the solid material is added with a nonionic surfactant F 108 and 5% of the total mass of solid materials in a 30wt% H2O2 aqueous solution. Next, the mixture was stirred with a glass rod until mixed evenly to obtain an MHNT-based geopolymer slurry, which was then poured into a cylindrical silica gel mold (diameter × height = 30 mm × 15 mm) and covered with plastic wrap to prevent water evaporation. The sample was left at room temperature to completely bubble and expand, and then transferred to a 60°C oven for rapid curing. After curing, the sample was removed from the mold and the sample was neutralized with an excess of 1M hydrochloric acid solution to remove excess alkali. Subsequently, the sample was washed several times with deionized water and dried overnight to obtain an MHNT-based porous foam geopolymer, recorded as MH 12 .

[0184] The dried MH 12 The sample was immersed in excess PDMS to make full contact with PDMS, and then the sample was placed in a heating and cooling state with a rate of 5 °C min -1 The samples were placed in a tube furnace and heated at 300 °C in an Ar gas environment. 12 .

[0185] The preparation method of the phase change composite material comprises the following steps:

[0186] PW was embedded in PMH by vacuum impregnation under the action of capillary attraction, surface tension, diffusion and adsorption. 12 Specifically, excess PW and prepared PMH 12 The geopolymer was placed in a glass beaker and placed in a vacuum oven at a temperature higher than the melting temperature of PW. After all PW was completely melted, the oven was evacuated for 1 h, during which PW could gradually penetrate into PMH. 12 Finally, the excess PW was removed with filter paper and the sample was cooled to obtain PW@PMH 12 Composite materials.

[0187] The phase change composite material obtained in this example was tested using the same leakage test and cycle stability performance test as in Example 1.

[0188] Example 13

[0189] The difference between this embodiment and embodiment 1 is that a calcination temperature of 800° C. is used in the process of preparing the geopolymerization active metahaloysite (step 1). The other synthesis steps are the same as those in embodiment 1.

[0190] The specific steps are as follows: calcining HNT at a high temperature of 800° C. in an air atmosphere to dehydroxylate HNT and obtain meta-haloysite (MHNT).

[0191] The MHNT and hollow glass microspheres are dispersed in the alkali activator (prepared in Example 1) at a mass ratio of 2:1, the mass volume ratio of the solid raw material to the alkali activator is 1:1.5, and the unit of the mass volume ratio is g:mL; then 0.25% of the total mass of the solid material is added with a nonionic surfactant F 108 and 5% of the total mass of solid materials in a 30wt% H2O2 aqueous solution. Next, the mixture was stirred with a glass rod until mixed evenly to obtain an MHNT-based geopolymer slurry, which was then poured into a cylindrical silica gel mold (diameter × height = 30 mm × 15 mm) and covered with plastic wrap to prevent water evaporation. The sample was left at room temperature to completely bubble and expand, and then transferred to a 60°C oven for rapid curing. After curing, the sample was removed from the mold and the sample was neutralized with an excess of 1M hydrochloric acid solution to remove excess alkali. Subsequently, the sample was washed several times with deionized water and dried overnight to obtain an MHNT-based porous foam geopolymer, recorded as MH 13 .

[0192] The dried MH 13 The sample was immersed in excess PDMS to make full contact with PDMS, and then the sample was placed in a heating and cooling state with a rate of 5 °C min -1 The samples were placed in a tube furnace and heated at 300 °C in an Ar gas environment. 13 .

[0193] The preparation method of the phase change composite material comprises the following steps:

[0194] PW was embedded in PMH by vacuum impregnation under the action of capillary attraction, surface tension, diffusion and adsorption. 13 Specifically, excess PW and prepared PMH 13 The geopolymer was placed in a glass beaker and placed in a vacuum oven at a temperature higher than the melting temperature of PW. After all PW was completely melted, the oven was evacuated for 1 h, during which PW could gradually penetrate into PMH. 13 Finally, the excess PW was removed with filter paper and the sample was cooled to obtain PW@PMH 13 Composite materials.

[0195] The phase change composite material obtained in this example was tested using the same leakage test and cycle stability performance test as in Example 1.

[0196] Embodiment 14

[0197] The difference between this embodiment and embodiment 1 is that a calcination temperature of 850° C. is used in the process of preparing the geopolymerization active metahaloysite (step 1). The other synthesis steps are the same as those in embodiment 1.

[0198] The specific steps are as follows: HNT is calcined at 850° C. in an air atmosphere to dehydroxylate the HNT and obtain meta-haloysite (MHNT).

[0199] The MHNT and hollow glass microspheres are dispersed in the alkali activator (prepared in Example 1) at a mass ratio of 2:1, the mass volume ratio of the solid raw material to the alkali activator is 1:1.5, and the unit of the mass volume ratio is g:mL; then 0.25% of the total mass of the solid material is added with a nonionic surfactant F 108 and 5% of the total mass of solid materials in a 30wt% H2O2 aqueous solution. Next, the mixture was stirred with a glass rod until mixed evenly to obtain an MHNT-based geopolymer slurry, which was then poured into a cylindrical silica gel mold (diameter × height = 30 mm × 15 mm) and covered with plastic wrap to prevent water evaporation. The sample was left at room temperature to completely bubble and expand, and then transferred to a 60°C oven for rapid curing. After curing, the sample was removed from the mold and the sample was neutralized with an excess of 1M hydrochloric acid solution to remove excess alkali. Subsequently, the sample was washed several times with deionized water and dried overnight to obtain an MHNT-based porous foam geopolymer, recorded as MH 14 .

[0200] The dried MH 14 The sample was immersed in excess PDMS to make full contact with PDMS, and then the sample was placed in a heating and cooling state with a rate of 5 °C min -1 The samples were placed in a tube furnace and heated at 300 °C in an Ar gas environment. 14 .

[0201] The preparation method of the phase change composite material comprises the following steps:

[0202] PW was embedded in PMH by vacuum impregnation under the action of capillary attraction, surface tension, diffusion and adsorption. 14 Specifically, excess PW and prepared PMH 14 The geopolymer was placed in a glass beaker and placed in a vacuum oven at a temperature higher than the melting temperature of PW. After all PW was completely melted, the oven was evacuated for 1 h, during which PW could gradually penetrate into PMH. 14 Finally, the excess PW was removed with filter paper and the sample was cooled to obtain PW@PMH 14 Composite materials.

[0203] The phase change composite material obtained in this example was tested using the same leakage test and cycle stability performance test as in Example 1.

[0204] like Fig.14As shown, it is a schematic diagram of the application of the PMH phase change composite material obtained by the present invention, which shows the application of the PW@PMH composite material in the building wall and the downstairs radiant heating system, wherein the PW@PMH composite material is directly used as the building wall or wrapped on the surface of the downstairs pipeline as a sandwich structure. When the ambient temperature is high (daytime or the water temperature in the pipeline is high), the PW@PMH composite material under the building wall / floor absorbs heat, making the indoor temperature relatively low. On the contrary, when the ambient temperature is reduced (nighttime or the water temperature in the pipeline is low), the PW in the PW@PMH composite material releases the stored heat, making the indoor temperature higher than the ambient temperature. Therefore, the PW@PMH composite material can balance the energy supply according to demand, greatly reduce indoor temperature fluctuations, and maintain a comfortable indoor temperature.

[0205] The technical solution of the present invention is not limited to the above-mentioned specific embodiments. All technical variations made according to the technical solution of the present invention fall within the protection scope of the present invention.

Claims

1. A method for preparing a porous geopolymer, characterized in that: The following steps are involved: S1, Preparation of geopolymer-active heliumite The halloysite is calcined in an air atmosphere to obtain meta-haloysite, which is denoted as MHNT; S2, Preparation of MHNT-based porous geopolymer foam by chemical foaming S2.1, dispersing MHNT and hollow glass microspheres in an alkali activator, adding a nonionic surfactant and a hydrogen peroxide aqueous solution, and mixing them evenly to obtain a MHNT-based geopolymer slurry; S2.2, pouring the MHNT-based geopolymer slurry into a mold, leaving it at room temperature until it is completely foamed and expanded, and then transferring it to an oven for curing, and obtaining a cured product after the curing is completed; S2.3, neutralizing the solidified product with an acid solution, washing and drying the product after neutralization to obtain a MHNT-based porous foam geopolymer, denoted as MH; S3: Superhydrophobic porous geopolymers obtained by vapor deposition of polydimethylsiloxane After MH is fully contacted with an excess of polydimethylsiloxane and then heated, a superhydrophobic porous geopolymer is obtained, which is denoted as PMH.

2. The method for preparing porous geopolymer according to claim 1, characterized in that: In the step S1, the calcination temperature is 650-850° C. and the calcination time is 3 hours.

3. The method for preparing porous geopolymer according to claim 1, characterized in that: In the step S2.1, the mass ratio of MHNT to hollow glass microsphere is (1-4):1; In the step S2.1, MHNT and hollow glass microspheres are both solid raw materials; The amount of the nonionic surfactant used is 0.1-0.5% of the total mass of the solid raw material; the concentration of the hydrogen peroxide aqueous solution is 30wt%, and the amount used is 5-10% of the total mass of the solid raw material; in the alkaline activator, the molar ratio of SiO2, Na2O, and H2O is 1.38:1:15.74; The mass volume ratio of the solid raw material to the alkali activator is 1:1.5, and the unit of the mass volume ratio is g:mL; In step S2.2, the standing time is 10-24 hours; the curing temperature is 50-80°C; In step S2.3, the acid solution is a 1M hydrochloric acid solution; deionized water is used for multiple washings during the washing process; the drying temperature is 60° C., and the drying time is 12 hours.

4. The method for preparing porous geopolymer according to claim 1, characterized in that: In step S2.1, the hollow glass microspheres are soda lime borosilicate glass microspheres with a diameter of 20-75 μm; the nonionic surfactant is F 108.

5. The method for preparing porous geopolymer according to claim 1, characterized in that: In the step S3, the heating process is carried out under the protection of an inert atmosphere, the heating temperature is 250-450° C., and the heating time is 3 hours.

6. A porous geopolymer prepared by the preparation method according to any one of claims 1 to 5.

7. A phase change composite material, characterized in that: The phase change composite material is obtained by encapsulating the phase change material in the porous geopolymer according to claim 6.

8. The phase change composite material according to claim 7, characterized in that: The phase change material is one of paraffin, stearic acid, lauric acid and myristic acid.

9. The phase change composite material according to claim 7, characterized in that: The packaging adopts a vacuum impregnation method.

10. Application of the phase change composite material according to any one of claims 7 to 9 in solar energy collection, heating, air conditioning, civil construction, and waste heat recovery.